2008
DOI: 10.1371/journal.pgen.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Alleles Influence Susceptibility to Invasive Aspergillosis

Abstract: Invasive aspergillosis (IA) is a common and life-threatening infection in immunocompromised individuals. A number of environmental and epidemiologic risk factors for developing IA have been identified. However, genetic factors that affect risk for developing IA have not been clearly identified. We report that host genetic differences influence outcome following establishment of pulmonary aspergillosis in an exogenously immune suppressed mouse model. Computational haplotype-based genetic analysis indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 53 publications
2
134
2
Order By: Relevance
“…Because of this, the laboratory mouse has been the experimental model of choice to study pathogenesis of infection, including innate and acquired host defense mechanisms. Inbred mouse strains differ significantly in their degree of susceptibility to infection with various human bacterial (eg, Mycobacterium tuberculosis, 15,16 Salmonella enterica, 17 Streptococcus pyogenes, 18 Streptococcus pneumoniae 19 ), fungal (eg, Histoplasma capsulatum, 20 Aspergillus fumigatus 21 ), protozoan (eg, Leishmania major, 22 Plasmodium berghei, 23 Plasmodium chabaudi 24 ), helminthic (eg, Schistosoma mansoni 25,26 ) as well as viral (eg, respiratory syncytial virus 27,28 ) pathogens. This attribute has been exploited to identify novel loci influencing resistance/susceptibility to infection and to provide new insight on host mechanisms involved in response to those pathogens that ultimately affect the onset, progression, and outcome of the infection.…”
mentioning
confidence: 99%
“…Because of this, the laboratory mouse has been the experimental model of choice to study pathogenesis of infection, including innate and acquired host defense mechanisms. Inbred mouse strains differ significantly in their degree of susceptibility to infection with various human bacterial (eg, Mycobacterium tuberculosis, 15,16 Salmonella enterica, 17 Streptococcus pyogenes, 18 Streptococcus pneumoniae 19 ), fungal (eg, Histoplasma capsulatum, 20 Aspergillus fumigatus 21 ), protozoan (eg, Leishmania major, 22 Plasmodium berghei, 23 Plasmodium chabaudi 24 ), helminthic (eg, Schistosoma mansoni 25,26 ) as well as viral (eg, respiratory syncytial virus 27,28 ) pathogens. This attribute has been exploited to identify novel loci influencing resistance/susceptibility to infection and to provide new insight on host mechanisms involved in response to those pathogens that ultimately affect the onset, progression, and outcome of the infection.…”
mentioning
confidence: 99%
“…131,132 Interestingly in humans, polymorphisms in chemokine ligand CXCL10 resulting in decreased DC CXCL10 production have been associated with increased risk of IA in HSCT patients. 22,133 Further studies, using DC vaccines to promote Th1 immunity, have shown promise in HSCT mouse models. 134,135 In these studies, adoptive transfer of DCs pulsed with A. fumigatus conidia or transfected with A. fumigatus conidial RNA induced the production of IFNg producing Th1 cells in mice following HSCT and increased resistance to A. fumigatus challenge.…”
Section: The Adaptive Immune Response To Aspergillosis In Hsct Patientsmentioning
confidence: 99%
“…19,21 Although these studies have largely relied on the use of BALB/C or C57BL6 mice, a comparison of 10 inbred mouse strains using the neutropenic model of IA revealed marked differences in their intrinsic susceptibility to A. fumigatus. 22 A haplotype-based computational genetic analysis wide-association study identified a correlation between survival of these mouse strains and polymorphisms in several genes including the gene encoding for plasminogen. 22 Further studies testing the role of these polymorphisms in the pathogenesis of IA have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has lead to a growing interest in host genetic differences that may contribute to the individual's risk of developing IFI. Recently, studies in HSCT populations have shown that polymorphisms in Toll-like receptor 4 [82] and genetic variations within the plasminogen allele may influence susceptibility to IA after transplant [83]. More research into host genetic influence on the risk of fungal disease following transplant is needed.…”
Section: Risk Factors Developing Invasive Fungal Infections Unique Rimentioning
confidence: 99%